Absolute rates of protein synthesis during meiotic maturation of mammalian oocytes in vitro. - Schultz, R M (1978)
Measurements of the rates of incorporation of [35S]methionine into protein and the specific activities of endogenous free methionine pools have been used to calculate the absolute rates of protein synthesis in mouse oocytes during spontaneous meiotic maturation in vitro. Fluorodinitro[3H]benzene was used to determine the specific activity of the oocyte's free methionine pool. It was found that the absolute rate of protein synthesis decreased from 43 to 31 pg/hr per oocyte during meiotic progression from dictyate to metaphase II (meiotic maturation), while the size of the intracellular free methionine pool decreased from 61 to 35 fmol per oocyte during the same period. Comparable measurements made on ovulated mouse oocytes that had undergone meiotic maturation in vivo strongly suggest that the decrease in the absolute rate of protein synthesis observed during meiotic maturation in vitro is physiologically significant. An alternative method that depends upon differential expansion of the oocyte's endogenous methionine pool was also used to determine absolute rates of protein synthesis. The results of these experiments are in excellent agreement with those obtained by using fluorodinitro[3H]benzene, indicating that the oocyte's free methionine pool is not compartmentalized.